High Order Thinking Skills (HOTS) Students In Solving Group Problem Based Gender - Rahayuningsih, Suesthi; Jayanti, Rani (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
This research aims to describe how students think based on high order thinking skills (HOTS) indicators based on gender. This research was a descriptive research with a qualitative approach. Data collection was done by task-based interviews. The interview revealed High Order Thinking Skills (HOTS) based on indicators analyzing, evaluating and creating. The data in this research was in the form of interviews and tests of group problems. To check the validity of the data triangulation was done. The triangulation done was time triangulation. This research involved 19 students, which consisted of 3 male students and 16 female students. The results of the research showed that the thinking ability of male students in solving group problems at the analysis stage was 66.67%, at the evaluation stage of 33.33% and at the creation stage of 0%. While the thinking ability of female students in solving group problems at the analysis stage was 62.5%, at the evaluation stage at 43.75% and at the creation stage of 0%. This shows that mastery of HOTS in the analysis aspect, male students are better than female students while in the evaluation stage female students are better than male students. And at the stage of creating. Male students get the same score as female students.